The Relationship of Caring Behaviors of Nurses with Post-Surgery Patient Anxiety in St. Ignatius and Pasuline Rooms of Santa Elisabeth Hospital Medan - Yuni Utami Ronauli Sinaga; Mestiana Br. Karo (Lembaga Pengembangan Kinerja Dosen, 2024)
Caring behavior is something that reflects humans which is manifested through affection, skills, self-confidence and responsibility. Anxiety is a painful and unpleasant condition characterized by feelings of fear, nervousness, restlessness and so on. The aim of this study is to analyze the relationship between nurses' caring behaviors and post-operative patient anxiety. The design used in this research is correlational using a cross-sectional approach. The population in this study are 128 respondents with the sampling technique being accidental sampling with a total of 47 respondents. The instruments in this research are the caring behaviors and anxiety questionnaire zung self-rating anxiety scale (SAS/SRAS). Data analysis in this study uses the Spearman rank test. The results of this study showed that the majority of respondents (57.4%) have a perception of nurses' caring behaviors in the good category and respondents (25.5%) experienced anxiety levels in the mild category, so that the results of the Spearman rank statistical test obtain p-value = 0.002 (p <0.005) which shows that there is a relationship between nurses' caring behaviors and post-operative patient anxiety in St. Ignatius and Pauline Hospital room of Saint Elisabeth Medan.